STRATEGIC TRANSFORMATION AND FINANCIAL PERFORMANCE: EVIDENCE AT PT. ASDP INDONESIA FERRY (PERSERO) - Syukron Sazly; Dirgahayu Erri; Diana Tambunan; Saddam Hussaen (Univesitas Muhammadiyah Tangerang, 2026)
This study examines the relationship between strategic transformation and performance enhancement at ASDP Indonesia Ferry during the 2017–2024 period. Using secondary data obtained from audited financial statements, annual reports, and publicly disclosed corporate strategies, the research adopts a longitudinal descriptive quantitative approach. The analysis focuses on key strategic initiatives, including operational restructuring, digital service transformation, route optimization, and asset management improvements. The findings reveal that ASDP’s transformation efforts are positively associated with improvements in financial performance, cost efficiency, service reliability, and overall operational effectiveness. In particular, digitalization initiatives and route rationalization contributed to better resource utilization and enhanced customer service quality. These results indicate that leadership-driven strategic transformation plays a crucial role in strengthening organizational performance and competitiveness within the maritime transport industryHowever, this study is limited by its reliance on secondary data and lack of primary stakeholder perspectives. Future research is recommended to incorporate qualitative insights and comparative analysis across similar state-owned enterprises. Overall, this study contributes to the literature on state-owned enterprise transformation and offers practical implications for policymakers and managers in improving performance sustainability.